1996
DOI: 10.1007/bf01457662
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear image analysis of immunohistochemically stained cells in breast carcinomas

Abstract: Hitherto, the relationship between malignancy-associated morphological features in single tumour cells and the expression of markers indicating functional properties of these cells remained widely unknown. This study was aimed at describing differences in the size, shape and chromatin structure between tumour cells with different marker expression for progesterone receptors (PgR) and p53. Two series of breast cancers, consisting of 50 PgR-positive, and 39 p53-negative and 49 p53-positive mammary carcinomas, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 20 publications
(13 reference statements)
2
14
0
Order By: Relevance
“…We, and many others, have shown that image analysis of nuclear features (size, shape, chromatin texture, and ploidy) can be prognostic for survival of breast cancer patients (Chapman et al, 2007). There have been previous reports of an association between p53 immunohistochemistry and nuclear features consistent with our observations, although a relationship with patient survival was not determined (Haroske et al, 1996; Friedrich et al, 1997). In this study we have shown that the protein based method and the DNA based method identify similar groups of patients with good and poor survival.…”
Section: Discussionsupporting
confidence: 88%
“…We, and many others, have shown that image analysis of nuclear features (size, shape, chromatin texture, and ploidy) can be prognostic for survival of breast cancer patients (Chapman et al, 2007). There have been previous reports of an association between p53 immunohistochemistry and nuclear features consistent with our observations, although a relationship with patient survival was not determined (Haroske et al, 1996; Friedrich et al, 1997). In this study we have shown that the protein based method and the DNA based method identify similar groups of patients with good and poor survival.…”
Section: Discussionsupporting
confidence: 88%
“…Oestrogen receptor-positive and -negative tumours could be distinguished on the basis of different nuclear features, such as area, DNA content, and certain texture features [16]. Other image cytometry studies showed that several features of nuclear contour and chromatin structure were signi®cantly different between breast tumour cells positive or negative for p53 or for progesterone receptor [17,18]. These ®ndings are interesting, because they show the ability of image cytometry to detect nuclear morphological changes which are related to the biology of the cell.…”
Section: Introductionmentioning
confidence: 99%
“…Local gray level differences and cell density combining with other morphological parameters are possible to follow cell culture development under various experimental conditions [29]. Hitherto, the relationship between malignancy-associated morphological features in single tumour cells and the expression of markers indicating functional properties of these cells remained widely unknown [65]. …”
Section: Tasks and Problemsmentioning
confidence: 99%